Disturbance observers and extended state observers for marine vehicles: A survey. (June 2022) - Gu, Nan; Wang, Dan; Peng, Zhouhua; Wang, Jun; Han, Qing-Long
Abstract: The operation performance of marine vehicles (MVs) is significantly vulnerable to external disturbances induced by wind, waves, and ocean currents in complex marine environments. Disturbance estimation is a fundamental issue in MV motion control, and various disturbance estimation methods are explored for high-performance motion control of MVs. This paper provides a comprehensive review of disturbance estimation methods developed for MVs. First, a three-degree-of-freedom nonlinear MV model is introduced. Next, two types of disturbance estimation methods in terms of disturbance observers and extended state observers are elaborated in detail. Then, applications of disturbance estimation methods in three MV motion control scenarios are discussed. Finally, six theoretical and technical issues on disturbance estimation methods for MVs are suggested for future investigations.